200 mm silicon carbide bulk growth optimisation: mass transport controlled by a designed gas deflector. (1st October 2022) - Tan, Peng; Kang, Wenyu; Yin, Jun; Kang, Junyong
Abstract: 200 mm silicon carbide bulk growth would be the mainstream in industrial production, but the difficulty of multiple physical fields control is increased with the larger diameter. In this study, a resistance heating based physical vapour transport system was established and explored for its appropriate parameters of multiple physical fields (such as thermal, velocity, flux and reaction components fields) by the COMSOL simulation. A combination of pressure at 5 torr and seed temperature of 2340 K was gained by taking the rate and homogeneity of in-plane growth into consideration. Furthermore, a gas deflector was designed to decrease the convection and to improve the homogeneity of mass transport. This gas deflector had the ability to enhance the quality and yield of 200 mm SiC crystal bulk. A high yield of 90.1% was achieved for the 200 mm part within the crystal thanks to this deflector (without the usage of the deflector was 38.5%). This work provides a useful tool and insights into the steps required for the optimisation of 200 mm or larger size SiC bulk growth.